Carbon isotope analysis and a solid state 13C NMR study of Mongolian lignite: Changes in stable carbon isotopic composition during diagenesis. (November 2017) - Erdenetsogt, Bat-Orshikh; Lee, Insung; Ko, Yoon-Joo
Highlights: Lower Cretaceous lignite samples studied. Correlation between carbon isotopic composition and chemical structure found. Mechanism controlling the changes in δ 13 C value of lignite proposed. Abstract: The results of a combined carbon isotope analysis and NMR study of a set of lignite samples from Mongolia show that a correlation exists between δ 13 C value and the ratios of oxygenated carbon (O-aliphatic, carboxyl/carbonyl and O-aromatic carbons) over protonated and carbon substituted aliphatic and aromatic carbons. The results indicate that the δ 13 C values of the lignite are controlled by two mechanisms: (i) Depletion in 13 C as a result of loss of isotopically enriched O-bonded carbons and (ii) enrichment in 13 C caused by a loss of isotopically depleted CH4 from aliphatic and aromatic carbons. At the rank of lignite, coal is enriched in 13 C because the amount of isotopically enriched CO2 and CO, released from coal as a result of change in chemical structure, is less than that of isotopically depleted CH4 .